2010
DOI: 10.1002/crat.200900662
|View full text |Cite
|
Sign up to set email alerts
|

Structure and electrical properties of Mg‐doped ZnO nanoparticles

Abstract: Mg x Zn 1-x O (x=0.01-0.3) nanoparticles were synthesized by the sol-gel technique using solutions of Mg and Zn based organometalic compounds. The electrical properties of Mg doped zinc oxide (ZnO) were studied within wide temperature range from 300 to 500 K under the N 2 gas flow (flow rate: 20 sccm) and in the frequency range from 40 Hz to 1 MHz for ac electrical measurements. The dc conductivities and the activation energies were found to be in the range of 10 -9 -10 -6 S/cm at the room temperature and 0.26… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(24 citation statements)
references
References 38 publications
1
23
0
Order By: Relevance
“…Hence, the correlated barrier hopping (CBH) is the dominant conduction mechanism. These results are consistent with previous reports obtained for Mg-doped ZnO [50], Zndoped SnO 2 [51] and Sn 2 O 3 -doped ZnO pellets [12]. In the CBH model, the electrons in the charged defect states hop over the Coulombic barrier whose height m W is given as:…”
Section: Ac Conductivity Studysupporting
confidence: 93%
“…Hence, the correlated barrier hopping (CBH) is the dominant conduction mechanism. These results are consistent with previous reports obtained for Mg-doped ZnO [50], Zndoped SnO 2 [51] and Sn 2 O 3 -doped ZnO pellets [12]. In the CBH model, the electrons in the charged defect states hop over the Coulombic barrier whose height m W is given as:…”
Section: Ac Conductivity Studysupporting
confidence: 93%
“…5, the relaxation frequency is shifted with respect to increase in temperature which is the sign or evidence of the Cole-Cole type relaxation mechanism in dielectric materials. 23 The activation energy of CdO nanomorphotypes are calculated by fitting the data through Arrhenius equation 29,30 …”
Section: The Complex Impedance Spectrummentioning
confidence: 99%
“…It also leads to an increase of the band gap energy which makes this compound a transparent material active in the ultraviolet region (UV). Furthermore, it can be exploited as a barrier material in quantum-well (QW) structures for electronic devices [7], but the electrical conductivity is decreasing by increasing the concentration of Mg. N. Kılınç et al [8] prepared ZnO powders doped with Mg by applying the sol-gel technique at room temperature, and showed that the conductivity decreased logarithmically with increasing Mg doping rate. Recently, many studies demonstrated that Al is one of the most intriguing candidates for replacing the traditional dopant Mg.…”
Section: Introductionmentioning
confidence: 98%